A fibrin gel-loaded Gouqi-derived nanovesicle (GqDNV) repairs the heart after myocardial infarction by inhibiting p38 MAPK/NF-κB p65 pathway - Huan-Huan Zhou; Xiaolei Zhou; Jianqiu Pei; Shiyin Xu; Biyu Jin; Jiuling Chen; Zixuan Zhang; Mingmeng Tang; Yan Liu; Andreas K. Nüssler; Liegang Liu; Qin Xu; et al. (Journal of Nanobiotechnology)
Abstract The restoration of cardiac function post-myocardial infarction (MI) remains a significant clinical challenge. Emerging evidence indicates that Goji berries (“Gouqi” in Chinese) and their extracts exhibit substantial cardioprotective properties. Here, we introduce fibrin gel-loaded Gouqi-derived nanovesicles (GqDNVs-gel) as a delivery system targeted at the infarcted myocardium. The application of GqDNVs-gel resulted in a marked improvement in survival rates over a 14-day period post-MI, enhanced cardiac function, reduced infarct size, myocardial apoptosis, and excessive fibrosis, and facilitated endogenous repair. Through a combination of transcriptomics and proteomics analyses, alongside in vitro and in vivo experiments, we identified that the cardioprotective effect of GqDNVs are mediated through the inhibition of the p38 MAPK-NF-κB p65 signaling pathway. Furthermore, GqDNVs contain abundant bioactive compounds, including proteins, genetic materials, lipids, polysaccharides, and flavonoids. GqDNVs-gel intervention can reshape the post-MI cardiac environment and modulate myocardial lipid metabolism, specifically impacting glycerophospholipid and α-linolenic acid metabolic pathways. The upregulation of the peptide Arg-Thr-Ile-Glu and the downregulation of phosphatidylethanolamine in the hearts of MI mice after GqDNVs-gel intervention may play crucial roles in modulating the associated metabolic pathways. This study is the first to highlight the multifaceted therapeutic effects of GqDNVs-gel, offering a promising strategy for enhancing cardiac function post-MI. Graphical abstract